2006
DOI: 10.1080/10715760600570547
|View full text |Cite
|
Sign up to set email alerts
|

AROS-29 is involved in adaptive response to oxidative stress

Abstract: Transient adaptation to mild oxidative stress was induced in human osteosarcoma cells chronically grown in sub-toxic concentrations of diethylmaleate (DEM), a glutathione (GSH) depleting agent. The adapted cells, compared to untreated cells, contain increased concentrations of GSH (4-6 fold) which, upon DEM withdrawal from the culture medium, return to normal values and are more resistant to subsequent oxidizing stress induced either by toxic concentrations of the same agent or by (H(2)O(2)) treatment. To inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Reactive oxygen species including hydrogen peroxide, superoxide anion, and singlet oxygen are generated as by-products of cellular metabolism primarily in mitochondria, and play a predominant role in many pathological conditions, including immune suppression, photo-carcinogenesis, and photo-aging [ 1 4 ]. Excessive generation of reactive oxygen species in the skin is a major contributor for various cutaneous pathologies [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species including hydrogen peroxide, superoxide anion, and singlet oxygen are generated as by-products of cellular metabolism primarily in mitochondria, and play a predominant role in many pathological conditions, including immune suppression, photo-carcinogenesis, and photo-aging [ 1 4 ]. Excessive generation of reactive oxygen species in the skin is a major contributor for various cutaneous pathologies [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…When their production exceeds the cell's antioxidant capacity, macromolecules such as lipids, proteins, and DNA can be damaged. 1 Excessive generation of ROS in the skin is believed to be an important contributor to a variety of cutaneous pathologies, including different types of cancers. 2,3 ROS such as superoxide anion, hydrogen peroxide, and singlet oxygen, also play a critical role in many pathological conditions, including immune suppression, photo-aging, and photocarcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, four SNPs located within TMEM161A were grouped into a haplotype block, and association analysis confirmed that both the SNPs and the haplotype were significantly associated with EN48 and EN60. TMEM161A, also known as adaptive response to oxidative stress protein 29 (AROS-29), is involved in several cellular processes, including the adaptive response to oxidative stress (Montesano Gesualdi et al, 2006), the response to ultraviolet radiation, and the response to retinoic acid; in addition, TMEM161A is a negative regulator of the intrinsic apoptotic signaling pathway in response to DNA damage and is a positive regulator of the DNA repair response. In birds, retinoic acid promotes embryonic development and egg production and can regulate the number of eggs (Fu et al, 2000;Scheider et al, 2018).…”
Section: Discussionmentioning
confidence: 99%